Can you believe? : hurricanes - Markle, Sandra; Bosson, Jo-Ellen, 1941- (New York : Scholastic, 2002)
Describes the causes, characteristics and destructive forces of hurricanes.
Includes bibliographical references (p. 48).
Keywords: Hurricanes -- Juvenile literature